The Outbreak of Diphtheria in Nigeria: the outcome of the nation’s low immunization coverage - Okoebor, Rita (Covenant Journal of Physical and Life Sciences, 2024)
The outbreak of diphtheria disease in Nigeria has claimed the lives of many Nigerians, and the country has the highest number of children who are not immunized. This study intends to investigate the outbreak of diphtheria disease in Kano State and the immunization practices of its citizens. A qualitative research method with the use of Focus group discussion was adopted in this study. Fifty-six homogeneous focus group discussions were conducted among four target populations: health workers, pregnant women, nursing mothers, and women with young children. Results revealed the outbreak of diphtheria, inadequacy of the health care system, non-utilization of modern health care services, poor immunization coverage and fear of the safety of immunization and vaccination by the inhabitants of the study communities. It was recommended that an adequate, well-equipped, and functional healthcare system with a highly motivated health workforce across the 774 local government areas in Nigeria be provided. Full-scale immunization and vaccination programs should be provided across villages and communities in the entire country, and citizens of Nigeria should be adequately sensitized to the signs and symptoms of immunization and vaccine-related diseases.